New Developments in Magnetic Resonance Imaging of the Brain - Koretsky, Alan P. (The American Society for Experimental NeuroTherapeutics, Inc., 2004)
Summary: Magnetic resonance imaging (MRI) continues to have a large impact on the diagnosis and management of a number of diseases, especially diseases associated with brain injury. The strengths of MRI are the unique contrast that can be obtained, and the fact that it is not harmful and that it can be readily applied to human and animal models. The past decade has seen development of functional MRI techniques that measure aspects of hemodynamics and water diffusion that are playing an important role. Indeed, these techniques are having a major impact on management of brain injury. The development of MRI continues at a rapid pace and a renewed push to increased spatial and temporal resolution will extend the applicability of anatomical and functional MRI. Increased interest in molecular imaging using MRI is increasing the number of processes that can be imaged in the brain. This work reviews some new developments that are being made in anatomical, functional, and molecular MRI of the brain, with comments about usefulness for work in the area of neuroprotection.